Penerapan Kepemimpinan Yesus Kristus dan Transformasi Sosial di Gereja - Desy Mahayani Arya; Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2024)
This paper aims to delve deeper into the concept of the leadership of Jesus Christ and analyze it is implications in the contemporary context, particularly within the church environment. From the research findings, it is found that the leadership of Jesus not only served as a model for His followers in His time but is also relevant and crucial to be applied in the context of Christian leadership today. This study highlights several key aspects of Jesus leadership, including His character, spirituality, and service. Jesus character in leadership inspires exemplary traits of love, devotion, humility, and integrity, forming the foundation for effective and positively impactful leadership. Furthermore, spirituality of Jesus in leading is reflected in His steadfastness in prayer and in His understanding and teaching of Scripture. Jesus service as a leader demonstrates His commitment to selflessly serve with love and prioritize the needs of others over His own. Through a qualitative approach, this research takes the Evangelical Fellowship Church of Eliezer in a specific region as a case study to illustrate how the application of Jesus leadership principles can yield positive social transformation in a church context. The findings of this research provide significant implications for contemporary church leaders to emulate Jesus leadership in serving the people with love, leading by example, and preparing the next generation grounded in spiritual values and integrity.